Reconstruction of the 1979-2005 Greenland ice sheet surface mass balance using satellite data and the regional climate model MAR - Fettweis, Xavier (2006)
In order to improve our knowledge on the current state and variability of the Greenland ice sheet surface mass balance (SMB), a 27-year simulation (1979-2005) has been performed with the coupled atmosphere-snow regional model MAR. This simulation reveals an increase in the main factors of the SMB which are, on the one hand, the snowfall (+ 1.6 ± 1.8 km3 yr-1) in winter and on the other hand, the run-off (+ 4.2 ± 1.9 km3 yr-1) in summer. The net effect of these two competing factors leads to a SMB loss rate of - 2.7 ± 3.0 km3 yr-1, which has a significance of 87%. The melt extent derived from the passive microwave satellite data since 1979 also shows this trend. The melt water supply has increased because the Greenland ice sheet has been warming up by + 0.09 ± 0.04 °C yr-1 since 1979. This warming comes from a uniform increase of downward infra-red radiation which can not be explained by the natural variability. These changes result very likely from the global warming induced by human activities. As a result, it seems that: i) increased melting dominates over increased accumulation in a warming scenario, ii) the Greenland ice sheet has been significantly losing mass since the beginning of the 1980's by an increasing melt water run-off as well as by a probable increase of iceberg discharge into the ocean due to the "Zwally effect" (the melt water-induced ice sheet flow acceleration) and iii) the Greenland ice sheet is projected to continue to lose mass in the future. The Greenland ice sheet melting could have an effect on the stability of the thermohaline circulation (THC) and the global sea level rise. On the one hand, increases in the freshwater flux from the Greenland ice sheet (glacier discharge and run-off) could perturb the THC by reducing the density contrast driving it. On the other hand, the melting of the whole Greenland ice sheet would account for a global mean sea level rise of 7.4 m. (PHYS 3)--UCL, 2006